Charge Transfer and Interface Effects in Co-Assembled Circular Donor Acceptor Complexes for Organic Photovoltaics - (:unkn) unknown (WILEY-V C H VERLAG GMBH, 2019)
An in-depth theoretical characterization of alternative structural architectures is reported for use in organic photovoltaic devices (OPV): a host-guest structure where a circular pi-conjugated nanohoop electron donor encapsulates an electron acceptor fullerene, forming a circular donor acceptor complex. The mesoscale morphology, pairwise charge transport at the donor or acceptor domains, and charge transfer reactions at the donor/acceptor interfaces are calculated. For a fundamental understanding, three prototype complexes are considered: C60@10-cycloparaphenylene (C60@[10]CPP), C70@11-cycloparaphenylene (C70@[11]CPP), C70@3-cycloparaphenyleneacetylene (C70@[3]CPPA). It is found that solid state packing is crucial for the interface morphology, charge transport, and the electronic performance of the materials. While contorted and stiff packing result in small structural disorder, electron-phonon coupling is reduced, charge mobility and charge transfer is limited by the complex transport network. In contrast, a regular packing arrangement suggests an efficient charge transport; however, it is limited by the large amount of disorder and relatively large electron-phonon coupling. Hole and electron mobilities in the order of 10(-3) to 0.1 cm(2) Vs(-1) and 10(-5) to 10(-2) cm(2) Vs(-1) have been extracted, respectively, and electron mobilities are found to be very susceptible to intermolecular arrangements. Power conversion efficiency of approximate to 10% under 1 sun illumination has been offered from time-domain drift diffusion model.
Keywords: fullerene; host-guest; mobility; nanohoops; organic photovoltaics; MOLECULAR-DYNAMICS SIMULATIONS; ELECTRON-TRANSFER; QUANTITATIVE PREDICTION; ENERGETIC DISORDER; TRANSPORT; CELLS; PERFORMANCE; MORPHOLOGY; EFFICIENCY; AMBER